Application of Label-Free Absolute Quantitative Proteomics in Human Gingival Crevicular Fluid by LC/MSE (Gingival Exudatome) - Bostanci, N; Heywood, W; Mills, K; Parkar, M; Nibali, L; Donos, N (Journal of proteome research, 2010)
Periodontal disease is perhaps the most common infectious disease in humans. Gingival crevicular fluid (GCF) is a local inflammatory exudate of the periodontal tissues. Its composition greatly varies between health and periodontal disease. GCF collection is rapid and noninvasive, but previous approaches aiming to analyze its composition have mainly involved single protein biomarkers. The aim of this study was to perform analysis of the GCF exudatome from healthy and periodontally diseased sites by LC/MSE, a label-free mass spectrometry method that enables simultaneous protein identification and absolute quantification in biological fluids. In total, 154 proteins of human, bacterial, and viral origin were identified in the 40 GCF samples obtained from the 10 subjects (five healthy and five generalized aggressive periodontitis). The proportion of bacterial, viral, and yeast protein was increased in disease, compared to health. The presence of host defense-related proteins, such as Cystatin-B and defensins, was confirmed to be present only in health. Among the newly identified GCF proteins were L-plastin detected only in disease (15.6 ± 12.1 fmol) and Annexin-1 detected in 5-fold higher levels in health. Nevertheless, pro-inflammatory cytokines or periodontal pathogen proteins were rarely detected. Conclusively, the LC/MSE technology may facilitate characterization of GCF proteome in periodontal health and disease, thus conferring prognostic and diagnostic value. Larger cohort studies are required to characterize the complete GCF proteome in health and disease.